2016
DOI: 10.2174/1874210601610010664
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chin-cup Therapy in Class III Malocclusion: A Systematic Review

Abstract: Background: The treatment of Class III malocclusion has been challenging for orthodontists. Among a plethora of treatment modalities, the chin-cup is considered a traditional appliance for early orthopedic intervention. Objective: The present study aims to investigate the current scientific evidence regarding the effectiveness of chin-cup therapy in Class III malocclusion of prognathic growing patients. Method: A systematic review of the literature was conducted using PubMed/Medline and the Cochrane Central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…The minimum sample size was calculated to be 66 patients ( n = 22 in each group) according to a study by Mousoulea et al, [3] assuming the standard deviation of the OHIP-14 score to be 4.62 and 6.08 in the control and monomaxillary groups, respectively, alpha = 0.05, and study power of 90%. To increase the reliability of the results, a minimum of 25 patients were evaluated in each group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum sample size was calculated to be 66 patients ( n = 22 in each group) according to a study by Mousoulea et al, [3] assuming the standard deviation of the OHIP-14 score to be 4.62 and 6.08 in the control and monomaxillary groups, respectively, alpha = 0.05, and study power of 90%. To increase the reliability of the results, a minimum of 25 patients were evaluated in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, class III malocclusion is defined as retrognathism of the maxilla or prognathism of the mandible or a combination of both. The prevalence of class III malocclusion is higher in Asian populations compared with Caucasians (23% versus 5%) [3]. Class III malocclusion is often associated with complex dentoalveolar problems including the edge to edge position of teeth or posterior cross-bite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews showed that there is considerable agreement between studies in that chin cup therapy may be used for interceptive treatment of growing Class III malocclusion based on short-term favorable results. 113 , 114 …”
Section: Treatment Of Developing Class III Malocclusionmentioning
confidence: 99%
“…Treatment in cases of extreme mandibular growth has been a challenge [ 6 , 7 ] and research has focused on the anatomy, histology and function of the TMJ [ 8 , 9 , 10 ] seeking the trigger of growth [ 11 ]. In experiments and in clinical practice, the mandible has been pushed backwards, mainly during the period of growth, for protrusion to alleviate [ 12 , 13 , 14 ]. Clinical observations of animal TMJs and the consequent suggestions after mandibular displacement have been heterogeneous and contradictory.…”
Section: Introductionmentioning
confidence: 99%